2014
DOI: 10.1111/pme.12535
|View full text |Cite
|
Sign up to set email alerts
|

How Patients' Self-Disclosure about Sickle Cell Pain Episodes to Significant Others Relates to Living with Sickle Cell Disease

Abstract: The results document to whom and how helpful it is to talk with others about SCD pain episodes and how SCD disclosure is related to strategies for managing this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
5
9
0
Order By: Relevance
“…Traditional in-person studies of support structures among patients with SCD found that informational and emotional social support in a community or family environment is positively associated with the patients' willingness to receive care and initiate disease-related therapy. 5 We observed a similar dynamic in SCD Unite. Thus, findings from this social media group not only underscore how involved family and friends are in the care and treatment of those living with SCD, but they also demonstrate that social support structures operate through a virtual medium similar to nonvirtual environments in the SCD community.…”
Section: Social Media Discussion Provide New Insight About Perceptiosupporting
confidence: 71%
See 1 more Smart Citation
“…Traditional in-person studies of support structures among patients with SCD found that informational and emotional social support in a community or family environment is positively associated with the patients' willingness to receive care and initiate disease-related therapy. 5 We observed a similar dynamic in SCD Unite. Thus, findings from this social media group not only underscore how involved family and friends are in the care and treatment of those living with SCD, but they also demonstrate that social support structures operate through a virtual medium similar to nonvirtual environments in the SCD community.…”
Section: Social Media Discussion Provide New Insight About Perceptiosupporting
confidence: 71%
“…Our prior analysis in the Sleep and Asthma Cohort (SAC) study, an unselected cohort of children with SCA (defined here as HbSS or HbSβ0 thalassemia), demonstrated that age was the only predictor of FEV 1 % predicted, with a decline of 0.3% for every additional year of age (−0.30; 95% CI, −0.56 to −0.05; P = 0.020) 5. Sex, asthma history, hemoglobin level, reticulocyte count, white blood cell count, incidence rate of severe acute pain requiring hospitalization, incidence rate of % predicted; (b) the strength of the association decreases as BMI percentile increases; and (c) at high values of BMI percentile, the association reverses and becomes negative, and FEV 1 % predicted declines because in the general pediatric population, with increasing total body fat percent, a negative slope is expected with decreasing FEV 1 % predicted values, after for adjusting age and sex.…”
mentioning
confidence: 99%
“…As such, it is imperative that the patient's and family's skills for coping with this illness are assessed and supported by expert clinicians from the time of diagnosis, while being reassessed and strengthened throughout the life of the patient. 32,33 While this might happen in the pediatric population, transition to adult care services remains a challenge. 7,34 The difficulties surrounding transitions of care are complex as well as well researched and discussed.…”
Section: Disease Experiencementioning
confidence: 99%
“…The research findings, which were acknowledged as modest, reported that patients with SCD were more likely to fully disclose pain and associated concerns to God and primary healthcare providers than to parents and close relatives or friends. The study also found that talking to God and parents was associated with improved psychological adjustment and that talking to healthcare providers and other relatives increased the willingness of a patient to see a doctor for pain episodes (Derlega et al, 2014).…”
Section: 6mentioning
confidence: 81%
“…In the USA, Derlega et al (2014) explored the relationship between living with SCD and self-disclosure of pain episodes to others and the implications of talking to others about pain episodes. The research findings, which were acknowledged as modest, reported that patients with SCD were more likely to fully disclose pain and associated concerns to God and primary healthcare providers than to parents and close relatives or friends.…”
Section: 6mentioning
confidence: 99%